On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom. - Parapar, Julio; Martin, Daniel; Moreira, Juan (Zootaxa, 2020)
The actual diversity of Terebellides (Annelida; Trichobranchidae) in the South East Atlantic Ocean remains largely unknown. Only two species have been reported to date, T. stroemii Sars, 1835 and T. jorgeni Hutchings, 2007. The revision of specimens collected during the Atlantide and Galathea oceanographic cruises in the Atlantic coast of Africa, along with new materials obtained during monitoring surveys off Gabon, Congo and Angola, has allowed us to describe seven new species: T. augeneri sp. nov., T. congolana sp. nov., T. fauveli sp. nov., T. kirkegaardi sp. nov., T. longiseta sp. nov., T. nkossa sp. nov. and T. ramili sp. nov. Moreover, the type material of Terebellides stroemii var. africana Augener, 1918 is redescribed and the variety raised to species. All taxa are morphologically characterised and compared with species described or reported in world seas, particularly from the Atlantic Ocean. The presence of T. stroemii in Africa and the validity of the thoracic uncini as taxonomic character is discussed and a key to all species of Terebellides described from the South Atlantic Ocean is provided. author email: julio.parapar@udc.es
World Polychaeta Database (WPolyDb). Closed access